CATEGORY OF «EDUCATION» IN PEDAGOGICAL DISCOURSE - Олександр Коберник; Галина Коберник; Ірина Білецька (Problems of Modern Teacher Training, 2021)
The purpose of the article is to reveal the traditional and modern approaches to the interpretation of the concept of “education” as a pedagogical category. Applying theoretical methods of research such as analysis, synthesis, induction, deduction, abstraction, comparison, generalization, systematization, classification, various scientists' approaches to the grounding of initial theoretical positions, systematization of views and approaches to the clarification of the leading pedagogical category have been considered. It is proved that there are different approaches to determining the essence of the category of “education” in pedagogy, which determines its ambiguity, versatility and heterogeneity of this phenomenon. For some scholars, it is understood as both influence and purposeful management, and as cultivation, and as an attachment to culture, and as a development of the semantic sphere, and as primary socialization. The most traditional is the idea of education as a process in which the leading role belongs to an adult who performs the functions of a caregiver and children are the objects of this upbringing. The modern view of education is based mainly on the progressive ideas of humanization, child-centrism, and the subject-subjective paradigm of upbringing, which treats it as subject-subjective interaction. Generalization of scientific sources indicates that the diversity of interpretations of the phenomenon of “education” is due to the presence of different methodological approaches, concepts of education, scientists and researchers ideas about the formation of personality, the role and place of the teacher and the pupil in education. Therefore, they as a social phenomenon, activity, system, action, value, process, interaction, interpret this concept. The prospects for further research on this problem of the educational theory are seen in the disclosure of concepts such as “the process of education” and “educational process”.